Enhancement of Material Quality of (Si)GeSn Films Grown by SnCl4 Precursor. (8th September 2015) - Mosleh, Aboozar; Alher, Murtadha A.; Cousar, Larry; Abusafe, Husam; Dou, Wei; Grant, Perry; Al-Kabi, Sattar; Ghetmiri, Seyed Amir; Alharthi, Bader; Tran, Huong; Du, Wei; Benamara, Mourad; et al.
Abstract : The (Si)GeSn films have been grown with and without carrier gases on Si substrate using a cold-wall ultra-high vacuum chemical vapor deposition system. Material characterization of the films grown with Ar carrier gas using X-ray diffraction and transmission electron microscopy shows achievement of higher quality films. Optical characterization of the films with photoluminescence shows enhancement in material quality of the films at 350 and 400ºC growth temperatures. Increase in the pressure results in higher Sn incorporation and higher photoluminescence intensity. Spectroscopic ellipsometry data confirms the change in the GeSn bandgap towards lower energies.